Do socio-demographic factors significantly impact depression treatment? - Llull Canellas, Aina Catalina (Medicinski podmladak, 2024)
Introduction: Depression is a common illness worldwide. Several studies have confirmed a tight relation between certain socio-demographic factors and the risk of undergoing depression.Aim: This study aims to find out which socio-demographic factors indicate a more unfavorable treatment outcome following depression assessment scales.Material and Methods: The research is a longitudinal study, retrospective in design which consists of two phases. Upon entrance, socio-demographic data (sex, age, marital status, occupation, and education level) and Hamilton Depression Rating Scale (HDRS or HAMD) scores of 30 participants were recorded. After a four-week treatment, HAMD scores were again recorded and compared with those obtained in the initial phase.Results: Patients with female gender, old age, employment, and low educational level as socio-demographic factors experienced weak changes in the HAMD scores. On the other hand, patients who claimed to be male, young aged, unemployed, and have higher education studies scored lower HAMD scores after treatment and, successfully obtained strong changes in the HAMD scores. Results for marital status were inconclusive.Conclusion: Female gender, aging, lower education and employment are factors that may have attributed to a poor treatment improvement and hence should be taken into consideration by general practitioners. Likewise, marital status resulted to be a statistically significant factor. However, no inclination towards a specific category was noticed.
Keywords: longitudinal study; Socio-demographic factors; depression